PEMBUATAN SISTEM PENGECEKAN KELULUSAN BERBASIS WEBSITE DI FAKULTAS TEKNIK UNIVERSITAS SURABAYA - Eduardus Aldo Kosasih; Budi Hartanto; Daniel Soesanto (CALYPTRA, 2018)
College students certainly want to graduate with the best results and on time or faster. Graduation checking system in the University of Surabaya, especially in the Engineering Faculty have not been able to completely follow the curriculum changes that occur. In addition, students have difficulties to check their prerequisite to graduate in their respective department. Until now, the system still using desktop-based application. It is difficult for students who do not have the app. Creating a graduation checking systemwebsite-based in the Engineering Faculty University of Surabaya aims to facilitate students to graduation prerequisite checks in each department. The system is made tocheckvarious aspects of the graduation requirements in each department. This system will compare the courses taken by students with courses that must be taken and ensure that students can graduate and fulfill all prerequisites with lectures contract. The trial results showed that students who use this system will be easier to check what are the prerequisites of graduation and find out what deficiencies unmet graduation prerequisite. Thus, administrative officer, Academic Advisor, and the Head of Department may determine the graduation of each student in each department more efficiently.